Phylogeography of the Habronattus amicus species complex (Araneae: Salticidae) of western North America, with evidence for localized asymmetrical mitochondrial introgression - Hedin, Marshal; Lowder, Michael C. (Zootaxa, 2009)
The frequency and significance of hybridization and gene introgression in spiders (Araneae) is unclear, largely because few studies have combined multiple lines of evidence in the study of systems where introgression is likely. Here we consider multiple types of data to gauge the prevalence and importance of mitochondrial introgression for three species of the Habronattus amicus species complex distributed in western North America. A comprehensive phylogeographic sample recovers some geographically-coherent mitochondrial clades, but conspicuously fails to resolve nominal species as monophyletic. This pattern of discordance between molecules and morphological taxonomy is studied in more detail for two species, H. amicus (Peckham and Peckham) and H. ustulatus (Griswold), found in syntopy on three dune systems in south-central Oregon. Here, multivariate morphological analyses clearly distinguish these two species, but also reveal a narrow window of size overlap between small H. amicus females and large H. ustulatus males. A quantitative assessment of microhabitat use shows that these species occupy different microhabitats at two of three dune systems, but that this difference breaks down at a single site (Summer Lake). Consistent with the size overlap and ecological data, mitochondrial data suggest interspecific gene flow at Summer Lake, which is apparently asymmetric from H. amicus into H. ustulatus. The introgression dynamics revealed in south-central Oregon impact our interpretation of mitochondrial gene trees for the entire species complex, and provide important insight into how hybridization may be influencing evolution in this diverse spider genus.